2018
DOI: 10.1186/s12891-018-1960-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological outcomes of arthroscopically assisted cannulated screw fixation for tibial eminence fracture in children and adolescents

Abstract: BackgroundThe purpose of this study was to determine the efficacy and complications of arthroscopically assisted reduction and fixation with cannulated screws for tibial eminence fracture in skeletally immature patients.MethodsThis was a retrospective case series study. Forty-eight patients who were skeletally immature at the time of tibial eminence fracture were treated in a tertiary children’s hospital between May 2004 and August 2015. Twenty-one patients were excluded due to non-operative treatment (n = 10)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…We had 17 concomitant meniscal injuries in 15 (22%) patients in our patient cohort. A recent study 20 found a similar 22% incidence of meniscal tear at the time of tibial spine avulsion repair in a smaller number of overall patients. However, a prior study found concurrent meniscal injury to be as low as 3.8%.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…We had 17 concomitant meniscal injuries in 15 (22%) patients in our patient cohort. A recent study 20 found a similar 22% incidence of meniscal tear at the time of tibial spine avulsion repair in a smaller number of overall patients. However, a prior study found concurrent meniscal injury to be as low as 3.8%.…”
Section: Discussionmentioning
confidence: 81%
“…22 However, an outcome comparison study determined that arthroscopic screw fixation yielded significantly better IKDC scores, lower incidence of postoperative glide pivot shift, and shorter operative times in comparison with suture fixation. 16 A recent study 20 has also determined that screw fixation was an effective method for treatment of tibial spine avulsion fractures with good clinical outcomes and few complications, although 100% of patients in the study (n = 27) underwent planned reoperations for hardware removal. A prior study 23 has also described a notable occurrence (5/13; 38%) of postoperative stiffness with suture fixation of tibial spine avulsion fractures, albeit this was in a young adult population in a small cohort of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…were found in the affected limb; thus, the clinical outcome was satisfactory. The key points of this technique are as follows: (1) synovial tissue and hematoma surrounding the fracture were debrided, and the bone bed was freshened to avoid affecting fracture reduction; (2) xation was performed using ACL tibial xators, with the anterior and medial edges of the fracture as the chosen xation sites. Fine Kirschner wires were used to establish the tunnels, and sutures were guided through the tunnels.…”
Section: E Cacy Evaluationmentioning
confidence: 99%
“…In adult patients, ACL tibial fractures are currently treated using cannulated screws, suture anchors, steel wires, high-strength sutures, and absorbable screws, with a satisfactory therapeutic e cacy in clinical reports. [2][3][4][5] However, as children are still growing and developing, and their treatment principles differ from those of adults, special techniques in fracture reduction and xation, with the aim of avoiding iatrogenic injuries to the epiphysis during surgery when possible, need to be developed. The suture binding technology is widely used for ACL tibial avulsion fracture at present.…”
Section: Introductionmentioning
confidence: 99%